PENGARUH METODE LATIHAN AKSELERASI SPRINT TERHADAP KECEPATAN PEMAIN SEPAKBOLA DI SSB PESPA PABEDILAN KIDUL - ramirez, ramirez; Firmana, Iif; Rahman, Ramdhani; Agustan, Boby (Journal of Physical Education and Sport Science, 2024)
Ramirez (NIM : 182223093), with the title "INFLUENCE OF SPRINT ACCELERATION TRAINING METHOD ON THE SPEED OF FOOTBALL PLAYERS IN SSB PESPA PABEDILAN KIDUL" The purpose of this study was to determine the effect of sprint acceleration training on the running speed of football players at SSB Pespa Pabedilan Kidul. This research method uses an experiment with One-Group Pretest-posttest research design with a population and sample of 18 SSB Pespa Pabedilan Kidul players, with sampling technique using saturated sampling so as to obtain a sample of 18 people, research method using quantitative research methods, normality test This data uses the Shapiro Wilk test with a significant value for pretest and posttest data 0.023 and 0.323 is greater than 0.05 then the data is normally distributed. The significant value for levene static is 0.447 > 0.05, then it is normally distributed. Furthermore, the value of Tcount obtained is 27,206 and for Ttable is 1,73961. Because the value of Tcount > Ttable, it can be concluded that there is an effect of sprint acceleration training on the speed of the football players of SSB Pespa Pabedilan Kidul Cirebon. Keywords: sprint acceleration, running speed, soccer